The pre-determinants of establishing immigrant women entrepreneurship in Lapland:Theory and practice - Yeasmin, Nafisa; Koivurova, Timo (Routledge, 2022)
The chapter focuses equally on immigrant entrepreneurship study and the socio-economic integration of female entrepreneurs in Lapland, an Arctic region located in northern Finland. This explorative study seeks pre-determinants for sustaining the existence of women entrepreneurs with migrant background. This paper attempts to understand what are the determinants that encourage women immigrants to embrace risks and uncertainties in establishing a business in such a sparsely populated region and whether there are small market opportunities for business. We interviewed immigrant women entrepreneurs (n = 18) for a critical evaluation based on their narrative stories and compare the existing situation in the light of entrepreneurship need for achievement theory for broadening our knowledge to better comprehend the complex phenomenon of women entrepreneurs with an immigrant background in Lapland.